Adherence to pharmacological treatment in hypertensive patients over 65 years of age - Tirado Rugel, Lesly Tatiana; Carvajal Chango, Gissel Katherine (Enfermería Cuidándote, 2026)
Arterial hypertension is considered a chronic non-communicable disease, associated with an unhealthy lifestyle, causing 9.4 million deaths per year worldwide. In underdeveloped countries, its prevalence is increasing and access to medication is decreasing, estimating a higher prevalence (8%) for the year 2030. Knowledge and adequate pharmacological treatment of this disease are important for its timely health control. There are several components involved in poor drug adherence such as different comorbidities, level of education, sex of the patients, among others. The purpose of this study is to investigate the factors related to adequate pharmacological adherence in older adults. This observational, descriptive and correlational study seeks to determine the relationship between sex, age, marital status and level of education with the level of pharmacological adherence. The sample consisted of 104 participants, where the highest percentage of hypertensive patients were women (77.9%). Eighty-eight point five percent had partial adherence and 11.5% had poor adherence to medication. There was no statistically significant association between the level of adherence and the sociodemographic variables of the participants. It is necessary to educate patients by stressing the importance of the continuity of pharmacological treatment to reduce or even prevent the development of other associated diseases.